1986
DOI: 10.1113/jphysiol.1986.sp015998
|View full text |Cite
|
Sign up to set email alerts
|

Lesions in the cat prepositus complex: effects on the vestibulo‐ocular reflex and saccades.

Abstract: SUMMARY1. The effects of bilateral electrolytic lesions within and around the prepositus hypoglossi (p.h.) nucleus on horizontal saccades in the dark and on the horizontal sinusoidal vestibulo-ocular reflex (v.o.r.) in the dark were studied.2. After p.h. lesion, including its rostral part between P 7 and P 8, the v.o.r. showed a phase lead as much as about 90 deg at 0-10 Hz. A significant gain reduction paralleled that phase lead at lower frequencies. A large post-saccadic drift was also observed, the time con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
2
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 42 publications
4
70
2
1
Order By: Relevance
“…Following lesions experimentally induced in the NPH, the cat was no longer able to maintain an eccentric position in its gaze. After each saccade, a centripetal exponential drift with a time constant of about 0-16 s was observed (Cheron et al 1986b;Cheron et al 1992;Mettens et al 1994). After cerebellectomy, the cat could not maintain its eyes in an eccentric position either.…”
mentioning
confidence: 99%
“…Following lesions experimentally induced in the NPH, the cat was no longer able to maintain an eccentric position in its gaze. After each saccade, a centripetal exponential drift with a time constant of about 0-16 s was observed (Cheron et al 1986b;Cheron et al 1992;Mettens et al 1994). After cerebellectomy, the cat could not maintain its eyes in an eccentric position either.…”
mentioning
confidence: 99%
“…Studies concerning eye movement deficits after electrical or chemical lesions in different premotor areas have proposed that the velocity-to-position integrator is located in the PH-vestibular nuclear complex (Cheron, Gillis & Godaux, 1986;Cheron, Godaux, Laune & Vanderkelen, 1986;Cannon & Robinson, 1987;Cheron & Godaux, 1987). The firing characteristics of premotor vestibular neurones, identified by means of intra-axonal labelling, have been reported to correlate with both eye position and velocity during ocular fixations and saccades, respectively (McCrea et al 1980;Yoshida, Berthoz, Vidal & McCrea, 1981;Berthoz et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular recordings of PH neuronal activity during spontaneous and vestibularly and visually evoked eye movements in monkeys and cats have shown the presence of cells encoding pure eye position (Ló pez- Barneo et al, 1982;Delgado-García et al, 1989) or related position velocity and velocity position signals (Ló pez- Barneo et al, 1982;DelgadoGarcía et al, 1989;McFarland and Fuchs, 1992). Moreover, permanent electrolytic lesions and transient pharmacological inactivations have shown that PH neurons are necessary for proper eye stability during positions of fixation (Cheron et al, 1986;Cheron and Godaux, 1987;Arnold et al, 1999;Moreno-Ló pez et al, 1996.…”
Section: Introductionmentioning
confidence: 99%